Article Withdrawal by ASERS Publishing - Fraudulent double submission and legal limitations - Rural Development through the Formation of Zonal Agro-Ecological Clusters - KASHIRSKAYA, Liudmila; VORONKOVA, Olga; SITNOV, Alexey; SHICHIYAKH, Rustem; KUDINOVA, Margarita; SYCHEVA, Irina (Journal of Environmental Management and Tourism; Vol 10 No 3 (2019): JEMT Volume X Issue 3(35) Summer 2019, 2019)
Today, the degree of agricultural development, and, in the future, the level of national food security, the public health and the quality of life, are largely ensured by innovative developments in the field of alternative agriculture, the preservation of natural resources and, above all, the main production facility – land. At the same time, the unfilled market capacity of organic products and the significant land potential for the development of organic farming create all the necessary prerequisites for enhancing the competitiveness of Russian rural producers. The development of agricultural entrepreneurship towards the greening of land use, organic production and development of the domestic market for organic (ecological) products in the format of zonal agro-eco clusters is one of the strategic directions for implementing reforms in the agricultural sector. The paper presents the directions of the formation and development of zonal agro-eco clusters for the production, processing and sale of organic products in the agricultural regions of Russia.